The Practice of Social Agents in Developing Kampoeng Ikan Community Groups, Kluncing Village, Banyuwangi - Yasir Muhyi; Nurul Hidayat (Faculty of Social Science, Universitas Negeri Malang, 2022)
The bad habits of the people of Kluncing Village in utilizing the river as a place to bathe, wash and toilet. Causing the river to experience pollution and damage. This condition eventually invited concern and care for two local figures to make changes until the formation of the Pokmas Kampoeng Ikan. This research is a descriptive study with a qualitative research approach. Determination of informants is done by purposive sampling or directly selected by the researcher. Furthermore, in data collection techniques, researchers used three data collection techniques including observation, interviews, and documentation. Researchers used Anthony Giddens' structuration theory as an analysis knife. The results of the study explain that there are various social practices carried out by agents in developing the Pokmas Kampoeng Ikan. Agents always strive to sensitize the surrounding community, providing examples, training and mentoring for beginners to learn proper freshwater fish farming. In addition to modeling actions, agents also routinely hold gatherings every two weeks and collaborate with various parties. The relationship between agent and structure shows the duality of structure that occurs through the schemes of significance, domination, and legitimacy